Menguak Eksistensi Pasar Tradisional dengan Keberadaan Pasar Modern di Kecamatan Krian Kabupaten Sidoarjo - Etak Anggraeni Hakim; Sony Kristiyanto (Economie: Jurnal Ilmu Ekonomi, 2020)
This study is based on the phenomenon of the development of modern markets in Indonesia, which are not only found in big cities but also in the surrounding sub-districts. This is likely to disturb the existence of pre-existing traditional markets. Traditional market management is also needed and must be maximized in facing the existence of this modern market. This research to determine the development of the Krian traditional market with the existence of Ramayana Mall and to find out the efforts to manage the Krian traditional market in the face of the existence of the Ramayana Mall. This research uses a qualitative approach with descriptive research type, data collection techniques using interviews, observation and documentation. The results of this research show that not all modern markets have eliminated the existence of traditional markets that have existed for a long time. Traditional markets can still compete strongly with the existence of modern markets. Many people use the Krian market to sell for a living to meet their daily needs. Efforts to manage the Krian market in dealing with the existence of Ramayana Mall are still minimal, even though to be able to better maintain the existence of traditional markets in facing modern markets that are nearby, good market managers are also needed to make them comfortable.